Desgaste abrasivo de revestimentos cralsin multicamada/gradiente - Teles, Vinícius Carvalho (2014)
PVD coatings have been used to improve the wear resistance of severe contacts in different tribological systems. Related works showed advantages in mechanical properties of multilayered and graded films due to their resistance to crack growth and better adhesion. During stamping, sliding between sheet metal and forming tool damages their surfaces. Maintenance of stamping tools involves polishing the tool edge, or, in case of severe damage, replacement of the tool. Hard coatings have been used on stamping tools in order to minimize these costly and time consuming operations. Sliding wear tests of CrAlSiN coatings applied by PVD onto tool steel have evidenced the occurrence of abrasive mechanisms on the worn surfaces, apparently caused by wear debris. In this work, the abrasion wear resistance of these coatings was investigated. The effect of substrate surface finish, coating architecture, coating composition and thickness was analyzed. Two different coating designs were used: multilayered and gradient coatings. In all the samples, the initial composition at the interface with the substrate was kept constant and the surface composition (CrN/AlSi ratio) was varied. The toughness of the coating was investigated by progressive load scratch tests. Free-ball microabrasion tests were carried out using SiC and SiO2. The wear resistance presented direct correlation to the product of the critical load and surface hardness. The wear rates of the multilayered coatings were higher than those of the gradient coatings. In microabrasion tests with SiC showed that coatings with higher concentration of AlSi near the surface presented the lowest wear rates. The gradient coatings had higher hardness and toughness than multilayer coating. When using SiO2 as abrasive particle the kc values showed indifferent to all coatings.